Structure, geometry and piezometry of the Turonian-Coniacian aquifer captured in the Benin-Togo Coastal Sedimentary Basin - Mellone Extraila, Glessougbe Cherguie; Abdoukarim, Alassane; Raoul Kpegli, Kodjo Apelete; Kissao, Gnandi; Chabi, Bio Guidah; Aoulatou, Alassane; Mama, Daouda; Boukari, Moussa (European Scientific Journal, ESJ, 2025)
The Kéta Basin in Benin and Togo is located in the tropical zone between the equator and the Tropic of Cancer, between parallels 6° 10’ and 7° 75’ north latitude and meridians 1° 0’ and 2° 48’ east longitude. The study area occupies the southern tip of the two countries, with the Mono River forming the border. The Turonian-Coniacian aquifer, the oldest aquifer unit in the coastal sedimentary basin, is the subject of this study. This study aims to determine the structure, geometry and piezometry of this aquifer. Three cross-sections were created (Benin and Togo) using the traditional method, combining topographical maps, graph paper and Qgis 2.18.15. Piezometry was then carried out in three stages: determining the altitudes of the measurement points, calculating the piezometric levels and interpolating the calculated piezometric levels. The piezometric map was produced using Excel, Surfer 11 and Qgis 2.18.15 in succession. All these methods indicate that the Coniacian Turonian aquifer outcrops to the north of the northern plateaus of the Benin-Togo Coastal Sedimentary Basin. As the flow direction is mainly north-south, it can be deduced that the aquifer is fed by rainwater infiltration at its outcrop areas.